2011
DOI: 10.1111/j.1526-100x.2011.00787.x
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale Patterns of Riparian Plant Diversity and Implications for Restoration

Abstract: Planning riparian restoration to resemble historic reference conditions requires an understanding of both local and regional patterns of plant species diversity. Thus, understanding species distributions at multiple spatial scales is essential to improve restoration planting success, to enhance long-term ecosystem functioning, and to match restoration planting designs with historic biogeographic distributions. To inform restoration planning, we examined the biogeographic patterns of riparian plant diversity at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 51 publications
1
26
1
Order By: Relevance
“…Tree and shrub plantings are used to restore forest overstory on reclaimed riparian areas, whereas passive processes are expected to recover understory vegetation. Similar to our findings, understory diversity in these riparian systems is attributable to a richer and more varied herb flora compared with the woody component (Viers et al ). McClain et al () found that understory composition of tree‐planted sites differed from that of mature riparian forests; however, relative cover of native species increased with greater canopy closure over time, accompanied by floristic shifts to more shade‐adapted species.…”
Section: Discussionsupporting
confidence: 91%
“…Tree and shrub plantings are used to restore forest overstory on reclaimed riparian areas, whereas passive processes are expected to recover understory vegetation. Similar to our findings, understory diversity in these riparian systems is attributable to a richer and more varied herb flora compared with the woody component (Viers et al ). McClain et al () found that understory composition of tree‐planted sites differed from that of mature riparian forests; however, relative cover of native species increased with greater canopy closure over time, accompanied by floristic shifts to more shade‐adapted species.…”
Section: Discussionsupporting
confidence: 91%
“…These results should encourage researchers to make further investigations of guild responses to water‐level regulation by including other stressors and other riparian guilds. An inclusion of herbs would increase the resolution since they are more diverse, more sensitive and responsive to flow changes than woody plants (Stromberg & Boudell ; Viers et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…We compared the understory vegetation sampled in abandoned channels (described above) with understory data from an existing 2003 study within the Sacramento River active channel floodplain (hereafter 'floodplain' data) that comprised 91 plots located within the same range of elevation relative to water surface and landform age as our abandoned channel plots (for details, see Vaghti et al, 2009 andViers et al, 2011). The previously surveyed floodplain plots were 200 m 2 .…”
Section: Floodplain Vegetation Data Setmentioning
confidence: 99%